PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 020 MUARA DANAU KECAMATAN KELAYANG - Septriani '; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve learning outcomes IPS class IV SDN 020 Muara Danau Kecamatan Kelayang through the implementation of cooperative learning model Student Teams Achievement Divisions (STAD). Pelakasanaannya process is done in the form of stages or cycles consisting of planning, implementation, observation and reflection. Subjects of this study amounted to 13 people, 4 boys and 9 girls. Based on the research application of cooperative learning model STAD can increase the activity of teachers. In the first cycle of meetings to-1 activity for teachers to get a 62.5% success with sufficient criteria. At the 2nd meeting increased to 79.17% with good criterion. In the second cycle to meeting all first gained 87.5% success criteria. At the 2nd meeting increased to 95.83% by qualifying was also very good. Student activity also increased in the first cycle to the meeting-1 activity students acquire 58.33% success with less criteria. At the 2nd meeting success of student activity is 70.83% with both criteria. In the second cycle to meeting all first gained success with an excellent 87.5%. At the 2nd meeting increased to 91.67%, with excellent qualifications. The implementation of cooperative learning model STAD also can improve student learning outcomes IPS from basic score (62.3) to UH I (69.62) has increased (11.74%). Basic score (62.3) to UH II (80) has increased (14,90%). It can be concluded that the model type STAD cooperative learning can improve learning outcomes IPS class IV SDN 020 Muara Danau Kecamatan Kelayang. Keywords: Model Cooperative Learning STAD, Learning Outcomes IPS